Pathogenetic features of acute naphazoline poisoning in children - Ekaterina S. Karpushkina; Olga A. Zhdanova; Galina A. Batishcheva; Yulia A. Petukhova (Belgorod National Research University, 2021)
Introduction: Acute poisoning by nasal decongestants is an important issue in pediatrics due to physiological and anatomical characteristics of the child's body and pharmacokinetics of drugs in early childhood. Epidemiology: The number of poisonings by this group of drugs ranged from 4% to 39% during the period from 2000 to 2018. All the studies reported that the most severe degree of intoxication was observed in children aged 1-3 years. Mechanism of action of nasal decongestants: The peculiarity of selective alpha2-adrenergic agonists is that when taken orally, misused or overdosed, they lose their selectivity for the target receptor. As a result, the drug causes acute poisoning and most often this effect occurs in children and adolescents. Clinical features and diagnostic criteria: Clinical signs of acute poisoning can appear both as a result of an overdose of the nasal decongestants and due to a therapeutic use of the drug according to the instruction. The symptoms are manifested by hypothermia, skin pallor, bradycardia, arterial hypotension, profuse sweating, and acrocyanosis. Imidazoline receptors and new opportunities: It is assumed that toxic effect of topical decongestants occurs not only by activation of alpha2-adrenergic receptors, but also through their influence on the selective imidazoline receptors. Based on the structure of these drugs, it is assumed that imidazoline receptors are the primary binding site for these drugs. Conclusion: Understanding the described mechanisms of alpha2-adrenergic agonist action and peculiarities of the child's symptoms in acute poisoning is necessary for the timely diagnosis and selection of the correct treatment strategy.